2002
DOI: 10.1046/j.1439-0434.2002.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Plasmodiophora brassicae and Arabidopsis thaliana: Parameters for Disease Quantification and Screening of Mutant Lines

Abstract: The soil‐borne obligate pathogen Plasmodiophora brassicae causes clubroot disease in species of Brassicaceae, including Arabidopsis thaliana. The host–pathogen interaction was studied with respect to the age of the plant at the time point of inoculation and to different infection pressures in order to establish a standardization of infection parameters and evaluation of disease extent for A. thaliana lines. Spore number per root weight, root and shoot weight of inoculated and non‐inoculated plants as well as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
134
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(138 citation statements)
references
References 78 publications
1
134
0
Order By: Relevance
“…Indeed, jasmonic acid may be acting as an antagonist of salicylic acid synthesis, as has been suggested by several researchers (Kunkel and Brooks 2002;Glazebrook et al 2003). The jar1 mutant was more sensitive to clubroot infection, according to Siemens et al (2002), and was also confirmed to be susceptible to the Australian population of P. brassicae. Induction of one lipoxygenase gene at 23 DAI has been shown by Siemens et al (2006), indicating a potential role for jasmonic acid during gall development (Ludwig-Müller and Schuller 2008).…”
Section: Genes Involved In Hormone Synthesis Signalling and Defencementioning
confidence: 56%
See 3 more Smart Citations
“…Indeed, jasmonic acid may be acting as an antagonist of salicylic acid synthesis, as has been suggested by several researchers (Kunkel and Brooks 2002;Glazebrook et al 2003). The jar1 mutant was more sensitive to clubroot infection, according to Siemens et al (2002), and was also confirmed to be susceptible to the Australian population of P. brassicae. Induction of one lipoxygenase gene at 23 DAI has been shown by Siemens et al (2006), indicating a potential role for jasmonic acid during gall development (Ludwig-Müller and Schuller 2008).…”
Section: Genes Involved In Hormone Synthesis Signalling and Defencementioning
confidence: 56%
“…As discussed in a recent review (LudwigMüller and Schuller 2008), according to the microarray analysis of Siemens et al (2006), several ethylene responsive genes were differentially expressed, clearly indicating a role for ethylene in clubroot development. Interestingly, the ethylene-resistant mutants (etr1-1 and etr1-3) and ethylene-insensitive mutants (ein3-1 and ein4) tested by Siemens et al (2002) did not show tolerance to clubroot. Resistance to P. brassicae infection was shown by Devos et al (2006) in the alh1 mutant defective in cross-talk between ethylene and auxin.…”
Section: Genes Involved In Hormone Synthesis Signalling and Defencementioning
confidence: 98%
See 2 more Smart Citations
“…Plants were evaluated in the stage of having at least three true leaves in water, in order to assess the infection degree precisely. The modified disease index (DI) following Siemens et al (2002) was calculated according to the formula DI = (0n 0 + 1n 1 + 2n 2 + 2n 3 ) × 100/3N t where: n 0 -n 3 -number of plants in the indicated class N t -total number of plants tested…”
Section: Plantmentioning
confidence: 99%